ANTI-CRISIS MANAGEMENT OF AGGREGATE FINANCIAL POTENTIAL OF UKRAINE - Portna, Oksana (Social Economics, 2018)
In the conditions of instability and changing financial and economic relations, adequate approaches to managing complex economic systems at all levels from micro to macro level, including the country's overall financial potential, are needed. All levels of government require appropriate approaches adapted to the difficult crisis conditions, which involve the consideration of the interdependence and interaction of many factors and components of financial and economic processes. The article presents the prerequisites for crisis management of the aggregate financial potential of Ukraine. The crisis financial and economic situation in Ukraine, the influence of many external and internal factors and components are considered. The approaches to crisis management of the combined financial potential of the country with the use of the achievements of world experience are offered. Modern challenges to managerial technologies are presented. The world practice of systematization of factors and components that influence the increase of the competitiveness of the economy as a factor of stabilization of the functioning of the national economy and its financial security component is considered. On this basis, financial-economic variables are outlined and argued. That can be used as analytical guidelines for effective management decisions when developing and implementing the principles of crisis management of the aggregate financial potential of Ukraine.The prospect of further research is the elaboration of practical anti-crisis measures to stabilize the functioning of the aggregate financial potential of Ukraine